MEANING IN TRANSLATION - Rini, Yulan Puspita (Universitas Islam Negeri Raden Intan Lampung, 2014)
Translation is a kind of process. It is not regarded as the product. The process of translation is decoding the source language text to find the meaning. After that, encoding the meaning in the target language text. The process of decoding and encoding meaning in the translation process is not a simple activity. there are many considerations that have to be taken into account. Meaning equivalence has to be maintained well. Because of that, decoding and encoding the meaning must be done properly. In finding the meaning of the source language text, it is not enough to pay attention merely on the referential meaning. the connotative meaning plays important role in gaining the right meaning. After getting the meaning of the source language text, maintaining meaning equivalence in target language can be difficult. There are problems that might rise the difficulty in finding the meaning equivalence. The problems are the difference of language system, the difference of culture, the various meanings embedded by a word, and the lack of generic-spesific word relationship.